TINGKAT KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR DESA BINA BARU KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Masnah; Adnan, Andi Astina; Sellang, Kamaruddin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to determine the level of human resource competency on the quality of public services at the Bina Baru Village Office, Kulo District, Sidenreng Rappang Regency and to determine the quality of public services at the Bina Baru Village Office, Kulo District, Sidenreng Rappang Regency. The population and sample in this research were 52 people who received services in May and June 2023 at the Bina Baru Village Office. The sampling technique used was a saturated sample. This type of research is quantitative descriptive. The data collection techniques used were observation, interviews, literature study and questionnaires. The data analysis technique used is descriptive statistics and with the help of the SPSS version 21 application. The research results show that the Human Resources Competency Level at the Bina Baru Village Office is in the